At-Tadhād fī Riwāyat “Hikāyat Al-Hubb” li Ghāzi Al-Qashaibiy (Dirāsat Dilāliyyat bi Manzhur John I. Saeed) - Muhammad Farhan Palowa; Abdul Muntaqim Al Anshory (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2022)
The aims of this research are to find out the forms of antonyms in Ghazi Al-Qashaibi's Hikayah Al-Hubb novel from the perspective of John I. Saeed. This type of research is descriptive qualitative research. The primary data source used is the novel Hikayah Al-Hubb by Ghazi Al-Qashaibi published by Dar As-Saqiy in 2011, while the secondary data sources consist of books, articles, and journals that support the discussion. The data collection techniques used are reading techniques and note-taking techniques. While the data analysis techniques used are, data reduction, data presentation, and drawing conclusions. The results of this study are the form of antonyms in the novel Hikayah Al-Hubb by Ghazi Al-Qashaibi based on the perspective of John I. Saeed is divided into five forms consisting of 14 simple antonyms, 5 gradable antonyms, 4 reverses antonyms, 6 converses antonyms, and 2 taxonomic antonyms.